The Influence of Work Culture, Work Experience and Work Ethics on Employee Performance at the North Sumatra Provincial Trade and Industry Office - Siti Hafsyah Permatasari; Soulthan Saladin Batubara; Juniarti Juniarti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The aim of this study is to determine if work culture has a positive and substantial influence on employee performance at the North Sumatra Provincial Department of Industry and Trade. Does work experience have a major and somewhat positive impact on employee performance at the North Sumatra Provincial Department of Industry and Trade? Does work ethics considerably and somewhat improve employee performance at the North Sumatra Provincial Department of Industry and Trade? Do work culture, work ethics, and work experience all have a substantial and positive impact on employee performance at the North Sumatra Provincial Department of Industry and Trade? A quantitative approach to data analysis is used using the SPSS program. In this paper, multiple linear regression analysis is used. The sample for the research consisted of 43 responders. To gather primary data, a questionnaire was used. The results of the research demonstrate that work culture has a favourable and substantial influence on employee performance at the North Sumatra Provincial Department of Industry and Trade. Work experience has a positive and considerable influence on employee performance at the North Sumatra Provincial Department of Industry and Trade. Work ethics have a favourable and considerable influence on employee performance at the North Sumatra Provincial Department of Industry and Trade. At the North Sumatra Provincial Department of Industry and Trade, work ethics, work culture, and work experience all have a positive and substantial effect on employee performance.